# Solve for y 2(7-3(1-y))+9=-2+2(6(y+1)-3y)

2(7-3(1-y))+9=-2+2(6(y+1)-3y)
Since y is on the right side of the equation, switch the sides so it is on the left side of the equation.
-2+2(6(y+1)-3y)=2(7-3(1-y))+9
Simplify -2+2(6(y+1)-3y).
Simplify each term.
Simplify each term.
Apply the distributive property.
-2+2(6y+6⋅1-3y)=2(7-3(1-y))+9
Multiply 6 by 1.
-2+2(6y+6-3y)=2(7-3(1-y))+9
-2+2(6y+6-3y)=2(7-3(1-y))+9
Subtract 3y from 6y.
-2+2(3y+6)=2(7-3(1-y))+9
Apply the distributive property.
-2+2(3y)+2⋅6=2(7-3(1-y))+9
Multiply 3 by 2.
-2+6y+2⋅6=2(7-3(1-y))+9
Multiply 2 by 6.
-2+6y+12=2(7-3(1-y))+9
-2+6y+12=2(7-3(1-y))+9
6y+10=2(7-3(1-y))+9
6y+10=2(7-3(1-y))+9
Simplify 2(7-3(1-y))+9.
Simplify each term.
Simplify each term.
Apply the distributive property.
6y+10=2(7-3⋅1-3(-y))+9
Multiply -3 by 1.
6y+10=2(7-3-3(-y))+9
Multiply -1 by -3.
6y+10=2(7-3+3y)+9
6y+10=2(7-3+3y)+9
Subtract 3 from 7.
6y+10=2(4+3y)+9
Apply the distributive property.
6y+10=2⋅4+2(3y)+9
Multiply 2 by 4.
6y+10=8+2(3y)+9
Multiply 3 by 2.
6y+10=8+6y+9
6y+10=8+6y+9
6y+10=6y+17
6y+10=6y+17
Move all terms containing y to the left side of the equation.
Subtract 6y from both sides of the equation.
6y+10-6y=17
Combine the opposite terms in 6y+10-6y.
Subtract 6y from 6y.
0+10=17
10=17
10=17
10=17
Since 10≠17, there are no solutions.
No solution
Solve for y 2(7-3(1-y))+9=-2+2(6(y+1)-3y)

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top